2017
DOI: 10.1038/srep45666
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Ambient Particulate Matter Induced COPD in a Rat Model and a Description of the Underlying Mechanism

Abstract: While the health effects of air pollution have been an international public health concern since at least the 1950s, recent research has focused on two broad sources of air pollution, namely, biomass fuel (BMF) and motor vehicle exhaust (MVE). Many studies have shown associations between air pollution PM and exacerbations of pre-existing COPD, but the role of air pollution PM in the development and progression of COPD is still uncertain. The current study indicates that rats can develop pronounced COPD followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 37 publications
8
75
0
Order By: Relevance
“…As shown by Kim et al, diesel exhaust particles, a major component of PM2.5, increase lung fibrosis, goblet cell hyperplasia, and inflammation in a mouse model . He et al found that chronic exposure to PM2.5 induced pronounced lower airway remodeling, mucus overproduction, and inflammatory cell infiltration in a rat model . Consistent with these findings, in the present study, PM2.5 exposure induced a marked increase in goblet cell hyperplasia and collagen deposition in the nasal mucosa that was significantly enhanced in CRS rabbits, suggesting that PM2.5 acted as an adjuvant in exacerbating remodeling changes in CRS.…”
Section: Discussionsupporting
confidence: 91%
“…As shown by Kim et al, diesel exhaust particles, a major component of PM2.5, increase lung fibrosis, goblet cell hyperplasia, and inflammation in a mouse model . He et al found that chronic exposure to PM2.5 induced pronounced lower airway remodeling, mucus overproduction, and inflammatory cell infiltration in a rat model . Consistent with these findings, in the present study, PM2.5 exposure induced a marked increase in goblet cell hyperplasia and collagen deposition in the nasal mucosa that was significantly enhanced in CRS rabbits, suggesting that PM2.5 acted as an adjuvant in exacerbating remodeling changes in CRS.…”
Section: Discussionsupporting
confidence: 91%
“…Until now, reports on MVE exposure to establish COPD models have not been widely recognized, and most of them indicated that the MVE exposure can decrease lung function and increase airway inflammation (He et al, 2017;Wright et al, 2005). However, it is still unknown exactly how the pulmonary vascular changes develop over time and whether these changes are related to the lung damage and airway inflammation.…”
Section: • What Is the Central Question Of This Study?mentioning
confidence: 99%
“…The environment conditions of the MVE exposure system and the changes in the concentration of PM and gas were according to the previously published protocol (He et al, 2017). The concentration of PM in the vehicle exhaust gas-exposed system measured using the TSI8533 particle analyser (TSI Inc., Shoreview, MN, USA) was as follows.…”
Section: Animals and Mve Exposurementioning
confidence: 99%
“…Liu et al, 2017). Study showed that in PM-induced rat model, many pathogenesis that related to COPD were activated, including pulmonary inflammation measured by bronchoalveolar lavage fluid (BALF) inflammatory cell counts, increased inflammatory cytokine expression in BALF and serum, emphysematous changes, airway remodeling and mucus metaplasia (He et al, 2017).…”
Section: Introductionmentioning
confidence: 99%